ESTETIKA KARYA SENI ILUSTRASI DOODLE ART KOTA MAKASSAR - Meisar Ashari; Nurwahidah Nurwahidah (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
Art is a work or human action that has a point of beauty that makes the human heart moved. In other words, art is an element of culture which aims to fulfill the needs of humans or community groups for aesthetic values. Doodle Art is a work of art that uses a lot of imagination and truth in processing and setting images on a medium. The purpose of this analysis is to find out the aesthetics of Makassar City Doodle Art Illustration Art works. For this reason, the target of the analysis is directed at the Makassar Doodle Art community, namely the millennial community of young people in Makassar City. This type of research is interpretive qualitative research and uses Monroe Breadsley's aesthetic theory approach which emphasizes elements of unity, complexity and seriousness. The population in this research is the Makassar Doodle Art community, totaling 50 people and the research sample is the Makassar Doodle Art Community, totaling 10 people. The data analysis techniques used are literature, video and photo documentation from existing samples, namely the Makassar Doodle Art community, Makassa city. The conclusion that can be presented in this article is that apart from the aesthetic concept, it is also about the process of creating illustrations (doodles) in the Makassar DoodleArt community. The process of creating Doodles using simple, improvised equipment can produce good work that can be analyzed.